Teoria winnicottiana do amadurecimento e da regressão para a compreensão do paciente hospitalizado regredido - Fonseca, Laura Barião da (2009)
The current dissertation aimed to present Winnicott s theories of personal development and regression to the understanding of the regressed hospitalized patient. As consequence, there was a general presentation of the theory of personal development of D. W. Winnicott, which emphasized on the early stages of matureness, the absolute dependency and relative dependency, because those are the phases when the association psyche-soma starts to develop, initiating the psychosomatic existence. Winnicott s ideas about regression to dependency and regression itself as a defensive organization are addressed as key points to the understanding and visualization of the possibilities for clinical management of the environment of this hospitalized patient regressed to the very primitive stages of matureness. The contextualization of the origins and functions of the hospital provides a better understanding of some aspects of the environment, which can be compared to those of the mother-environment in the early mother-infant relationship. The functions of the mother during this period, when well adapted to the needs of the baby, facilitate certain events promoting the integration of psychosomatic unity. The absolute adaptation to the needs of the regressed hospitalized patient can be observed in some aspects of the ambient hospital. The research about Winnicott s theories of development and regression can provide the hospital clinic psychologist Professional a better understanding of the regressed hospitalized patient, grounding the work of this Professional and others in theory an also tecknically, in the clinical care of the hospitalized patient